Missed nursing care and related factors: a cross-sectional study - Rahimeh Khajoei; Mohadeseh Balvardi; Tayebeh Eghbali; Mahboubeh Sadat Yousefi; Mansooreh Azizzadeh Forouzi (BMC Nursing)
Abstract Background Nurses facing numerous responsibilities in hospitals are often forced to prioritize nursing care. Missed nursing care affects nurses’ ability to effectively manage, oversee, and assess patient care interventions and may contribute to unfavorable patient outcomes. Awareness of missed nursing care is essential for improving patient care and nursing performance and optimizing the work environment. Research on the factors contributing to missed nursing care is essential for implementing targeted strategies. This study aimed to determine missed nursing care and its related factors in Iran. Methods This cross-sectional study involved 189 nurses. Two questionnaires on missed nursing care and related factors were used for the data collection. Mann-Whitney U test and one-way ANOVA or Kruskal-Wallis test were used to analyze the data. Results The mean (SD) of nurses’ age was 31.19 (6.4). The mean of missed nursing care was 6.4 (SD = 31.1), which was higher than the median of the questionnaire. The most frequently reported missed care was toilet monitoring (23.3%) and setting up food (19.6%). The total mean score of factors related to missed nursing care was 11.6 (SD = 68.7), which was lower than the median of the questionnaire. The factors related to missed nursing care included engaging the nurse with other actions (76.7%) and an inadequate number of staff (76.2%). There was a significant association between the mean MNC score and participants’ age (P < 0.001), work experience (P = 0.002), and employment type (P < 0.001). Conclusion Given the severe nursing shortage and its potential negative impact on patients, healthcare management and policymakers need to address missed nursing care. Proposed solutions to alleviate the nursing staff shortage include enhancing the work environment, increasing nurse recruitment opportunities, and improving their compensation and benefits packages. Additionally, there is a need for governmental and hospital initiatives to enhance the working conditions through increased financial investment and support programs for nurses. Management should focus on minimizing nurses’ non-essential responsibilities and supporting efforts to reduce missed nursing care occurrences.